The performance of Djallonke sheep fed on diets containing various proportions of cocoa pod husk and 5 percent NaOH-treated maize cobs - Tuah, A.K.; Obese, F.Y.; Orskov, E.R.; Okai, D.B.; Adomako, D.; Amaning, K.O.; Said, A.N.; Greenhalgh, J.F.D. (1995)
In three experiments five diets which contained O, 150, 300, 450 and 600 g kg-1 of cocoa pod husk (CPH) and 600, 450, 300, 150 and 0 g kg-1 of treated maize cobs were evaluated. The other ingredients were wheatbran, cotton seed cake, dicalcium phosphate, NaCl and a trace mineral and vitamin premix. The ingredients were milled through a 6 mm sieve. In the first experiment (growth rate studies) 50 yearling Djallonke females weighing 5-13 kg were allocated randomly to the five diets, and dry matter intake, body-weight gain and feed conversion efficiency were determined. In a second experiment (metabolism studies) five young weaned Djallonke ram lambs weighing 5-11 kg were fed on each of the five diets in a Latin-square design. Feed intake, apparent digestibility coefficients of dry matter and organic matter and digestible dry matter and digestible organic matter intakes were measured. In a third experiment, the diets were also given to five fistulated adult wethers (Djallonke X Sahel) in a Latin-square design, and rumen pH was measured from 1 to 12 h and also 24 h after feeding. In the growth rate studies, dry matter intake significantly increased from 73 g kg-1 W0.75 to a maximum of 101 g kg-1 W0.75 as the proportion of CPH increased from 0 to 600 g kg-1 diet, but growth rates (ranging from 37 to 55 g per day) and feed conversion efficiency were not significantly affected by dietary treatments. In the metabolism studies, feed intake increased with increasing levels of CPH in the diet, but intakes of digestibile dry matter and degestible organic matter were not significantly affected by the dietary treatments. The apparent digestibility coefficients of dry matter and organic matter were significantly affcted by the dietary treatments, with increase in COH level reducing the values. The rumen pH, although low perhaps because of the grinding of the ingredients, was not the cause of the low digestibility of the CPH-containing diets.